Influence of Magnetic Wood on Mechanical and Electromagnetic Wave-Absorbing Properties of Polymer Composites - Satish Geeri; B. Krishna Murthy; Aditya Kolakoti; M. Murugan; P. V. Elumalai; N. R. Dhineshbabu; S. Prabhakar (International Journal of Polymer Science)
The application of wireless electronic devices is increasing nowadays; hence, there is a necessity for electromagnetic wave-absorbing material, which is mechanically stable. Polymer composites with magnetic wood as filler material were fabricated by hand lay-up methods of 6 mm thickness. For the proposed immersion duration, magnetic wood was developed by in situ chemical co-precipitation methods. The microwave absorbing phenomenon is evaluated based on the complex permeability, complex permittivity, dielectric tangent, and magnetic tangent losses. The experimentation was done by vector network analyzer in the frequency range of 8.2–12.4 GHz by X-band and Through-reflect-line (TRL) calibration. It was observed that the reflection losses increase as the immersion time increases from −8.70 dB to −9.30 dB at the frequency range of 10.2 GHz. A similar trend is also followed for the mechanical properties like tensile strength, bending strength, and impact strength with respect to the immersion time. The results revealed that the best mechanical and electromagnetic absorption properties are obtained for the specimens with immersion time of 72 hours. Validation is done for the electromagnetic wave-absorbing properties and mechanical properties by regression analysis, and the experimental data are in close agreement with the regression data.